Motor Cortex Microcircuits (Frontiers in Brain Microcircuits Series) - Takehsi Kaneko; Gordon M. G Shepherd; Michael Brecht; Nicholas Hatsopoulos (Frontiers Media SA, 2015)
How does the motor cortex enable mammals to generate accurate, complex, and purposeful movements? A cubic millimeter of motor cortex contains roughly ~10^5 cells, an amazing ~4 Km of axons and ~0.4 Km of dendrites, somehow wired together with ~10^9 synapses. Corticospinal neurons (a.k.a. Betz cells, upper motor neurons) are a key cell type, monosynaptically conveying the output of the cortical circuit to the spinal cord circuits and lower motor neurons. But corticospinal neurons are greatly outnumbered by all the other kinds of neurons in motor cortex, which presumably also contribute crucially to the computational operations carried out for planning, executing, and guiding actions. Determining the wiring patterns, the dynamics of signaling, and how these relate to movement at the level of specific excitatory and inhibitory cell types is critically important for a mechanistic understanding of the input-output organization of motor cortex. While there is a predictive microcircuit hypothesis that relates motor learning to the operation of the cerebellar cortex, we lack such a microcircuit understanding in motor cortex and we consider microcircuits as a central research topic in the field. This Research Topic covers any issues relating to the microcircuit-level analysis of motor cortex. Contributions are welcomed from neuroscientists at all levels of investigation, from in vivo physiology and imaging in humans and monkeys, to rodent models, in vitro anatomy, electrophysiology, electroanatomy, cellular imaging, molecular biology, disease models, computational modeling, and more.
English
Keywords: Motor Cortex; intracortical connectivity; corticospinal neurons; directional tuning; motor control